The Impact Of Customer Complaint Resolution Time On The Number Of Network Complaints At Pt XYZ: An Experimental Study On The Implementation Of Complaint Handling Technology (SOC Platform) - Darmanto, Putri Melati (Eastasouth Institute, 2025)
This study examines the influence of the Service Operation Center (SOC) Platform on customer complaint resolution time and network-related complaint volume at PT XYZ. Using a quasi-experimental study design and Difference-in-Differences (DID) analysis, data were collected from PT XYZ customer complaint system for one year. The study compares regions using the SOC Platform (treatment) with regions not using it (control) to measure the effect of quicker complaint resolution on complaint volume. The result mirrors that the application of the SOC Platform significantly improved complaint resolution times and reduced complaint volume. These findings show that the adoption of digital solutions, such as the SOC Platform, can enhance service quality, reduce operational inefficiencies, in order to raise customer satisfaction for the telecommunication sector.